2015
DOI: 10.1111/tri.12630
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic arteries of the human liver - anatomical variants and surgical relevancies

Abstract: SummaryThe purpose of our study was to investigate the anatomical variations of the extrahepatic arterial structures of the liver with particular attention to rare variations and their potential impact on liver surgery. A total of 50 human abdominal organ complexes were used to prepare corrosion casts. A multicomponent resin mixture was injected into the abdominal aorta. The portal vein was injected with a different colored resin in 16 cases. Digestion of soft tissues was achieved using cc. KOH solution at 60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
1
16
0
3
Order By: Relevance
“…Many hepatic artery variants described in the CRL classification could not be defined in Michels' or Hiatt's classification. Neglecting aberrant hepatic arteries may increase the risk of iatrogenic injury to the aberrant arteries and result in liver ischaemia, biliary ischaemia, liver abscess or biliary–enteric anastomotic failure. For instance, most of the blood supply to the extrahepatic biliary tree comes from the RHA or rRHA.…”
Section: Discussionmentioning
confidence: 99%
“…Many hepatic artery variants described in the CRL classification could not be defined in Michels' or Hiatt's classification. Neglecting aberrant hepatic arteries may increase the risk of iatrogenic injury to the aberrant arteries and result in liver ischaemia, biliary ischaemia, liver abscess or biliary–enteric anastomotic failure. For instance, most of the blood supply to the extrahepatic biliary tree comes from the RHA or rRHA.…”
Section: Discussionmentioning
confidence: 99%
“…Michels found that standard extrahepatic arterial anatomy occurs in 55–60% of individuals based on results of 200 autopsies. Recent meta-analyses and large volume surgical, radiological, and post-mortem anatomical studies including up to 12,000 cases each, reported an extrahepatic arterial anatomic variation ranging from 10% to 42% [8] , [9] , [10] , [11] , [12] , [13] .…”
Section: Discussionmentioning
confidence: 99%
“…An aGDA has not been reported in literature. In a meta-analysis of CA variations which included 12,000 cases from 36 studies, there was no mention of a replaced GDA (rGDA) [2,7]. Many other studies have identified frequency of variations in origin of rGDA, summarised in Table 1 [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Origin Of Gdamentioning
confidence: 99%
“…A thorough knowledge of arterial anatomy and its variations is a key prerequisite for safe hepatopancreaticobiliary (HPB) surgery . So frequent are arterial variations that it is impossible to consider any one anatomical description as normal .…”
Section: Introductionmentioning
confidence: 99%